The Evolution of Paleoecology. (April 2020) - Napier, Joseph D.; de Lafontaine, Guillaume; Chipman, Melissa L.
Abstract : While the interplay between migration and adaptation dictates species response to climate change, technological limitations have obfuscated explicit tests on past adaptive responses. However, a surge in technology-driven advances in paleoecological methods coincides with breakthroughs in processing ancient DNA, providing the first opportunity to assess adaptation to past climate shifts.